Pengaruh Carbopol 940 Sebagai Gelling Agent terhadap Karakteristik Gel Ekstrak Daun Belimbing Wuluh (Averrhoa bilimbi L.) - Lourensia Amelia Agatha (Prodi D3 Farmasi Politeknik Katolik Mangunwijaya, 2024)
Starfruit (Averrhoa bilimbi L.) is a plant widely used by people as a traditional medicine. Starfruit leaves are known to contain flavonoid compounds that have antibacterial activity, so they have the potential to be used in the treatment of skin infections. In this study, starfruit leaf extract was formulated in the form of a gel preparation, with the addition of the gelling agent Carbopol 940. This study aimed to determine the effect of variations in the concentration of Carbopol 940 (0.5%, 1%, and 1.5%) on the physical characteristics of starfruit leaf extract gel. Tests were carried out through organoleptic, homogeneity, viscosity, pH, spreadability, adhesiveness, and protective power. Data were analyzed using the Shapiro–Wilk normality test and Levene's homogeneity test. If the data were normally distributed and homogeneous, a One Way ANOVA test was performed followed by an LSD test at a 95% confidence level; otherwise, the Kruskal–Wallis and Mann–Whitney tests were used. The analysis results showed significant differences (p < 0.05) in viscosity, spreadability, and adhesion parameters between the three formulas, as well as differences in protective power between formulas I and III. The best formula based on all parameters was formula II.